Relationship between Capital Allocation Efficiency and Diversification Strategy from the Perspective of Internal Control - Jingjuan Wang; Weili Xia (Discrete Dynamics in Nature and Society)
Based on the quality of internal control, this study discusses the impact of internal control quality on resource allocation in the internal capital market and how capital allocation efficiency affects strategic decision-making. If the quality of internal control can be correctly evaluated and included into the management's strategic decisions, the enterprise can improve the efficiency of capital allocation and formulate an appropriate development strategy. Using panel data from the Shanghai and Shenzhen stock markets from 2013 to 2017, we investigate the relationship among overall internal control information quality, capital allocation efficiency, and enterprise strategic decision-making. The results show that when the level of free cash flow is high, the incentive mechanism of corporate governance increases the possibility of diversification; the lower the quality of internal control information is, the more likely it is for enterprises to pursue diversification; improving the quality of internal control helps management to allocate internal resources reasonably. When the efficiency of capital allocation is high, it can effectively prevent diversification. This study contributes by revealing the mechanism of the impact of internal control quality on strategic decision-making and expands the relationship between internal control and corporate strategic management.